sp2 carbon allotropes in elastomer matrix: From master curves for the mechanical reinforcement to lightweight materials - M. Galimberti; G. Infortuna; S. Guerra; V. Barbera; S. Agnelli; S. Pandini (eXPRESS Polymer Letters)
This work presents high surface area sp2 carbon allotropes as important tools to design and prepare lightweight materials. Composites were prepared based on either carbon black (CB) or carbon nanotubes (CNT) or hybrid CB/CNT filler systems, with either poly(1,4-cis-isoprene) or poly(styrene-co-butadiene) as the polymer matrix. A correlation was established between the specific interfacial area (i.a.), i.e. the surface made available by the filler per unit volume of composite, and the initial modulus of the composite (G′γmin), determined through dynamic mechanical shear tests. Experimental points could be fitted with a common line, a sort of master curve, up to about 30.2 and 9.8 mass% as CB and CNT content, respectively. The equation of such master curve allowed to correlate modulus and density of the composite. Thanks to the master curve, composites with the same modulus and lower density could be designed by substituting part of CB with lower amount of the carbon allotrope with larger surface area, CNT. This work establishes a quantitative correlation as a tool to design lightweight materials and paves the way for large scale application in polymer matrices of innovative sp2 carbon allotropes.